(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
Community empowerment actually refers to the word empowerment, which is an effort to actualize the potential that is already owned by the community. Thus, the approach of community empowerment in the development of palm sugar farming communities is the emphasis, on the importance of self-reliant local communities, as a system that organizes themselves. Such a community empowerment approach is certainly expected to give a role to individuals not as objects, but as actors who determine their lives. Community empowerment efforts can be seen from the side of their existence as a process. Empowerment as a process can be seen from the stages of activities in order to achieve a goal, which is usually determined by the time period. Society in English terms is a society that comes from the Latin word socius which means (friend). The term community comes from the Arabic word which means (toÂ participate and participate). Society is a group of people who get along with each other, in scientific terms it interacts with each other. A human entity can have infrastructure through which its citizens can interact with one another. Another definition, society is the unity of human life that interacts according to a particular system of customs which is continuous, and which is bound by a sense of shared identity. Continuity is a community unity that has all four characteristics, namely: Interaction between its citizens, customs, continuity of time, a strong sense of identity that binds all citizens. The most important factor that must be considered in carrying out community empowerment programs is that without business capital it is very difficult for the community to be able to improve their standard of living. Empowering people is not enough just to provide venture capital but must be accompanied by an increase in the capacity of human resources so that they are able to think and act in making various efforts and efforts to improve their welfare independently without any dependence on others. The provision of facilities and infrastructure for the community to be able to do their business is one part of the government’s responsibility which must be carried out through community empowerment programs. Keywords: Empowerment, Community, Business Capital, Facilities and Infrastructure.